Frequency Deviation-Free Compound Control Strategy for Seamless Mode Transfer in Microgrids Based on VSG - Zhou, Yu; Chen, Chen; Ou, Chuangang; Liu, Mingxiang; Zhao, Jingtao (Frontiers in Energy Research, 2022)
Virtual synchronous generator (VSG) is widely applied in microgrid technology due to its ability to withstand the impact of grid connected inverters without inertia. The frequency deviation in the droop control of VSG has a reducing effect on the hosting capacity of the microgrid. Therefore, this paper proposes a VSG based frequency deviation-free control strategy. When the microgrid is in the island/grid connected switching operation mode, it will result in violent fluctuations of the active power on condition that there is a reactive and fast power change. Therefore, the delay characteristic of synchronous generator is introduced into VSG to achieve a smooth transition of reactive power and steady-state value that lowers the impact on the system. The rotational inertia is a fixed value, which may fail to meet certain control requirements of the microgrid, such as suppressing power oscillation and rapidly recovering frequency. The fixed moment of inertia is later on improved to an adaptive inertia moment that can effectively solve the problem of rapid rise and fall of frequency as well as improve on the frequency response of microgrid. Finally, the simulation model is established by MATLAB to verify the effectiveness and feasibility of the proposed control algorithm.